Mast Cells and MCPT4 Chymase Promote Renal Impairment after Partial Ureteral Obstruction - Pons, Maguelonne; Ali, Liza; Beghdadi, Walid; Danelli, Luca; Alison, Marianne; Madjène, Lydia Celia; Calvo, Jessica; Claver, Julien; Vibhushan, Shamila; Åbrink, Magnus; Pejler, Gunnar; Poli-Mérol, Marie-Laurence; et al. (Frontiers in Immunology, 2017)
Obstructive nephropathy constitutes a major cause of pediatric renal progressive disease. The mechanisms leading to disease progression are still poorly understood. Kidney fibrotic lesions are reproduced by a model of partial unilateral ureteral obstruction (pUUO) in newborn mice. Based on data showing significant mast cell (MC) infiltration in patients, we investigated the role of MC and murine MCPT4, a MC-released chymase, in pUUO using MC- (Wsh/sh), MCPT4-deficient (Mcpt4-/-) and wild-type (WT) mice. Measurement of kidney length and volume by magnetic resonance imaging (MRI) as well as post-mortem kidney weight revealed hypotrophy of operated right kidneys (RK) and compensatory hypertrophy of left kidneys (LK). Differences between kidneys were major for WT, minimal for Wsh/sh and intermediate for Mcpt4-/-mice. Fibrosis development was focal and increased only in WT-obstructed kidneys. No differences were noticed for local inflammatory responses, but serum CCL2 was significantly higher in WT versus Mcpt4-/- and Wsh/sh mice. Alpha-smooth muscle actin (αSMA) expression, a marker of epithelial myofibroblast transformation (EMT), was high in WT, minimal for Wsh/sh and intermediate for Mcpt4-/- RK. Supernatants of activated MC induced αSMA in co-culture experiments with proximal tubular epithelial cells. Our results support a role of MC in EMT and parenchyma lesions after pUUO involving, at least partly, MCPT4 chymase. They confirm the importance of morphologic impairment evaluation by MRI in pUUO.